Pengaruh Kualitas Produk, Harga dan Pelayanan terhadap Tingkat Penjualan pada PT. Kurnia Garam Sejahtera di Kota Padang - Prayuda, Toha; Yulasmi, Yulasmi; Karlinda, Ai Elis (Lembaga Yasin AlSys, 2025)
The influence of product quality, price and service on sales levels at PT. Kurnia Garam Sejahtera in Padang City, under the guidance of Mr. Dr. Yulasmi, S.E., M.M and Mrs. Ai Elis Karlinda, S.E., M.M. This research aims to determine and try to analyze the influence of product quality, price and service on sales levels at PT. Karnia Garam Sejahtera in Padang City. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this research are consumers of PT. Karnia Garam Sejahtera in Padang City. The research results found that there was a positive and significant influence between product quality and sales levels. There is a negative and significant influence between Price and Sales Level. There is a positive and significant influence between Service and Sales Level. There is a joint influence of Product Quality, Price and Service on Sales Levels.